Sex differences between serum uric acid levels and cardiovascular outcomes in patients with coronary artery disease after stent implantation - Yuan, Song Lin; Kim, Moo Hyun; Lee, Kwang Min; Jin, Xuan; Song, Zhao Yan; Park, Jong-Sung; Cho, Young-Rak; Lim, Kyunghee; Yun, Sung-Cheol (Frontiers in Cardiovascular Medicine, 2023)
Objective: The relationship between elevated serum uric acid (SUA) levels and cardiovascular outcomes after stent implantation remains uncertain. This study sought to evaluate the impact of SUA on 12-month cardiovascular outcomes after stent implantation. Methods: We performed a retrospective study of patients who successfully underwent stent implantation and enrolled 3,222 patients with coronary artery disease (CAD) from a single center. SUA levels were measured before stent implantation. The patients were divided into six groups (< 4, 4 - 4.9, 5 - 5.9, 6 - 6.9, 7 - 7.9 and ≥ 8mg/dL) at SUA intervals of 1.0 mg/dL. The incidence of cardiovascular outcomes in the six groups was monitored for 1 year after stent implantation and the hazard ratios were estimated. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) for cardiovascular outcomes were estimated using a Cox proportional hazard regression analysis. The primary endpoint was all-cause death. The secondary endpoint was a composite of all-cause death, myocardial infarction, target vessel revascularization, stent thrombosis and stroke. The follow-up duration was 12 months. Results: Over the 12-month follow-up period, there were 101 all-cause deaths and 218 MACCE. After adjustment for several parameters, the group with SUA levels of more than or equal to 8 mg/dL had significantly higher hazard ratios in the incidence of all-cause death or MACCE. The group with less than 4.0 mg/dL had significantly higher hazard ratios in all-cause death only in male patients. In contrast, there were no significant differences observed for cardiovascular outcomes in female patients. Conclusions: Our study identified a U-shaped association between SUA levels and cardiovascular outcomes during 12-month follow-up for males, but not for females. Further studies are warranted to clarify the sex differences between SUA levels and clinical outcomes.